ANALYSIS OF BANK INDONESIA RATE OF RETURN ON ASSETS AT THE PT. BANK MANDIRI TBK MANADO - Deisy Natalia Lalujan; Frendy A.O. Pelleng; Tinneke Tumbel (Universitas Sam Ratulangi, 2016)
ABSTRACT: This study aimed